Status and development of high-power laser facilities at the NLHPLP. (2018) - Zhu, Jianqiang; Zhu, Jian; Li, Xuechun; Zhu, Baoqiang; Ma, Weixin; Lu, Xingqiang; Fan, Wei; Liu, Zhigang; Zhou, Shenlei; Xu, Guang; Zhang, Guowen; Xie, Xinglong; et al.
Abstract : In this paper, we review the status of the multifunctional experimental platform at the National Laboratory of High Power Laser and Physics (NLHPLP). The platform, including the SG-II laser facility, SG-II 9th beam, SG-II upgrade (SG-II UP) facility, and SG-II 5 PW facility, is operational and available for interested scientists studying inertial confinement fusion (ICF) and a broad range of high-energy-density physics. These facilities can provide important experimental capabilities by combining different pulse widths of nanosecond, picosecond, and femtosecond scales. In addition, the SG-II UP facility, consisting of a single petawatt system and an eight-beam nanosecond system, is introduced including several laser technologies that have been developed to ensure the performance of the facility. Recent developments of the SG-II 5 PW facility are also presented.